Validation of a technique by high-performance liquid chromatography for the determination of total isoflavones - Pilar A. Soledispa Cañarte; Migdalia Miranda Martínez; Viviana García Mir (GarVal Editorial Ltda., 2017)
Context: Isoflavones may act as selective regulators in the prevention of various diseases. The most important source of isoflavones is the soy, from which different phytotherapeutics are elaborated of use in Ecuadorian population. However, its concentration varies depending on several factors, therefore quality assessment need to be carried out through out several analytical methods. Aims: To validate an analytical method by high precision liquid chromatography (HPLC) to quantify total isoflavones in herbal medicine. Methods: To quantify isoflavones, it was used a brand liquid chromatography with UV/VIS detector at 260 nm, C-18 column using isocratic method. The mobile phase was composed of 2% acetic acid: acetonitrile (75:25). The quantification was performed against reference standard. The parameters for the validation followed the established in the USP 33. Results: The chromatogram presented six peaks with elution between 1.557 and 18.913 min. The linearity of the system and the method got r2 equal to 0.98 and 0.99 respectively. The coefficients of variation 1.5% in the study of repetitiveness and 2% in intermediate precision. The accuracy of the adjusted lineal model exhibited r=0.95 and intercept reliable interval (-0.921; 1.743). Conclusions: The validated method was specific, accurate, precise and linear. It can be used for quality control and stability studies of isoflavones present in herbal medicine.